A pilot study of dialectical behavioral therapy group skills training in patients with substance use disorder: changes in substance use severity, mood and relationship skills - Bilican, F. Işıl; Çetinkaya, Mustafa; Çelebi, Elif; Gülen, Birgül; Barham, Huzeyfe (Journal of Dependence, 2022)
Objective: This pilot study aimed to investigate effects of Dialectical Behavior Therapy Group Skills Training (DBT-ST) on patients’ severity of substance use status, mood and other psychological symptoms, difficulties in emotion regulation, interpersonal problem solving skills, and social competence. Method: Nine outpatient males with substance use disorders were administered the DBT-ST for 20 weeks. Age ranged between 17 and 34. Average years of substance use was 1.61 (SD=.29). DBT-ST modules (mindfulness, emotion regulation, interpersonal skills, and distress tolerance) were administered for 20 weeks. Urine toxicology screenings, the Addiction Profile Index (API), the Symptom Check List-90-Revised (SCL-90-R), the Beck Depression Inventory (BDI), the Difficulties in Emotion Regulation Scale (DERS), the Interpersonal Problem Solving Inventory, and the Perceived Social Competence Scale were administered at pre and post-treatment. Results: There were significant decreases in the severity of substance use with decreased number of positive drug screening test results and an increase in emotion regulation; decreases in the API total score, dependency diagnosis, and the effects of substance use on the user sub-scale scores; depression, hostility, and phobic anxiety sub-scale scores on the SCL-90-R; the BDI total score; and nonacceptance, strategies, clarity and impulsivity sub-scale scores of the DERS. Conclusion: The findings indicated a 20 week DBT-ST helped participants increase their days of abstinence, regulate emotional regulation, decrease depressive and anxiety symptoms, and substance related difficulties.